Management for Sustainable Resources - Environmental Challenges. Communication and Sense of Awareness: Array - Zeca, Ecaterina Daniela; Dragomir Bălănică, Carmelia Mariana; Stoica, Maricica (Acta Universitatis Danubius. Communicatio, 2020)
Human, in his stay on the planet, tormented by existential anguish, goes to and forth for having food and shelter, then more food and bigger shelters, fast and then faster vehicles, good medicines and more resistant to diseases. , more productive animals and plants. Man has moved beyond the natural systems that had existed in equilibrium. Aware of his power, his intelligence, human prefers to forget that the struggle for survival is a game with zero sum, one survives on the other. Economic growth has become a religion: it solves many, but not the ethical dilemmas. Dilemmas, part of them have names: Global Warming, Overpopulation, Pollution, Climate Change, Natural Resource Depletion, Loss of Biodiversity, Deforestation, Ocean Acidification, Acid Rain, Ozone Layer Depletion, Water Pollution, Urban Sprawl, Public Health, Genetic Modification of Food.